An Antiracist/Antioppressive Framework for Social Work Supervision: The SHARP Framework Applied to Reflective Supervision. - Godwin, LaShonda; Tennor, Maura; Howard, Allison; Beegle, Christopher S; Meringolo, Claire; Shaia, Wendy (Social Work, 2026)
Social work supervisors have the power to shape the next generation of social workers. Thus, it is imperative that social work supervision take an antiracist/antioppressive approach to effect transformational change for the individuals and families with whom we work rather than supporting and maintaining systems and practices that cause harm. This article proposes applying the SHARP (structural oppression, historical context, analysis of role, reciprocity and mutuality, and power) framework to reflective supervision (RS) for this purpose. RS emphasizes important factors for social work supervision such as collaborative meaning making and emotional learning. However, alone, RS does not explicitly address the pervasive issues of racism and oppression that inevitably show up in social work practice. Therefore, authors apply the SHARP framework to RS to promote critical consciousness, mutual accountability, and transformational social work practice. This article introduces the SHARP framework and RS, outlines how each component of SHARP enhances RS, and suggests practical applications.